Perspective article: flow synthesis of functional materials - Sebastian, Victor; Khan, Saif A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2017)
Continuous-flow synthesis of specific functional materials is now seen as a reliable synthesis approach that gives consistent product properties. This perspective article aims to survey recent work in some of the relevant areas and to identify new domains where flow synthesis of functional materials can be better than the conventional synthesis methods. It also emphasizes the need for developing high-throughput integrated synthesis and screening systems for almost all functional materials so that laboratory-scale recipes can be transformed into reliable manufacturing processes. New areas relevant to functional materials which have remained unexplored in flow synthesis are also highlighted.